Studi Kasus Treatment Kapur Tohor Terhadap pH Air Pada Settling Pond Di Pit 72 PT Unirich Mega Persada - Roby Cahyadi; Stephani Sandan; Eni Framita, (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This research aims to determine the level of effectiveness of quicklime content treatment using the dissolved and sprinkled method, in the treatment of acid mine drainage at PT Unirich Mega Persada. The research method used is a case study with quantitative experimental research, where the sample consists of lime content of 0.1 gram, - 1 gram. There are also samples of 21 liters of acid mine water, 10 liters of water for the dissolved method, 10 liters of water for the sprinkled method and 1 liter of water to determine the pH of acid mine water without quicklime treatment.So the results of this research obtained a pH value of 6-10.5 with a lime content of0.1 gram/liter -1 gram/liter, with a lime requirement of 25.5 kg/m3 for the dissolved method, there is also a pH value of 5-9.6 with a lime content of 0.1 gram/liter -1 gram/liter, with a lime requirement of 76.5 kg/m3 for the sprinkled method. From the results of the pH values of the 2 methods of using lime to neutralize acid mine water, both can actually increase the pH. However, with the same lime content, we found a more effective pH value with a low lime content of 0.1 gram/liter, namely the pH 6 dissolution method.